Mg-Protoporphyrin IX Signals Enhance Plant’s Tolerance to Cold Stress - Zhang, Zhong-Wei; Wu, Zi-Li; Feng, Ling-Yang; Dong, Li-Hua; Song, An-Jun; Yuan, Ming; Chen, Yang-Er; Zeng, Jian; Chen, Guang-Deng; Yuan, Shu (Frontiers in Plant Science, 2016)
The relationship between Mg-protoporphyrin IX (Mg-Proto IX) signals and plant’s tolerance to cold stress is investigated. Arabidopsis seedlings grown for 3 weeks were pretreated with 2 mM glutamate and 2 mM MgCl2 for 48 h at room temperature to induce Mg-Proto IX accumulation. Then cold stress was performed at 4 °C for additional 72 h. Glutamate + MgCl2 pre-treatments alleviated the subsequent cold stress significantly by rising the leaf temperature through inducing Mg-Proto IX signals. The protective role of glutamate + MgCl2 treatment was greatly compromised in the mutants of Mg-Proto IX synthesis, Mg-Proto IX signaling and cyanide-resistant respiration. And the enhancement of cold-responsive gene expression was greatly compromised in the mutants of Mg-Proto IX synthesis, Mg-Proto IX signaling and ABA signaling, but not in the mutant of cyanide-resistant respiration. Cold stress promoted cyanide-resistant respiration and leaf total respiration exponentially, which could be further induced by the glutamate + MgCl2 treatment. Mg-Proto IX signals also activate antioxidant enzymes and increase non-enzymatic antioxidants (glutathione but not ascorbic acid) to maintain redox equilibrium during the cold stress.